Real-time prediction and updating method for LEO satellite handover based on time evolving graph - Xin HU; Hangyu SONG; Shuaijun LIU; Xiuhua LI; Weidong WANG; Chunting WANG (Tongxin xuebao)
In order to solve the problem of low handover efficiency raised by the interwined impacts of time-varying topology of LEO satellites and terminal movement,a real-time satellite handover prediction framework based on time evolving graph and a shortest path dynamic updating method was proposed.This framework dynamically updated the handover prediction results from the temporal and spatial dimensions according to the terminal movement.The simulation results show that the framework can effectively improve the accuracy of the forecast and avoid the unnecessary handover.